If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 3q = -10 + -10q + -7 Reorder the terms: 9 + 3q = -10 + -7 + -10q Combine like terms: -10 + -7 = -17 9 + 3q = -17 + -10q Solving 9 + 3q = -17 + -10q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '10q' to each side of the equation. 9 + 3q + 10q = -17 + -10q + 10q Combine like terms: 3q + 10q = 13q 9 + 13q = -17 + -10q + 10q Combine like terms: -10q + 10q = 0 9 + 13q = -17 + 0 9 + 13q = -17 Add '-9' to each side of the equation. 9 + -9 + 13q = -17 + -9 Combine like terms: 9 + -9 = 0 0 + 13q = -17 + -9 13q = -17 + -9 Combine like terms: -17 + -9 = -26 13q = -26 Divide each side by '13'. q = -2 Simplifying q = -2
| 1.3x-3.4=0.5x+1.48 | | 3x+7=-2(2x+4)+1 | | 5+6x=25 | | (3x+y)(x^2+3x+4y)= | | 3-0.125=-2 | | 5y+4x=10+8 | | -10b=3-9b | | 3n=7(8n+7) | | 9y+4x=9+4 | | 2z^2+z+50=0 | | 12-6t=2t-8 | | 4m-4=3+3m | | 6+1.9n=24 | | 5y-(6y+9)=11 | | 4x-2=14-2x | | -3+5u+4=-9+4u | | 9r=-1+10r | | 6x+7y=4 | | 0.33-6=-8 | | 20-5(4x+2y)= | | (2b-8)(3b-7)= | | 6-6x^2= | | 6h-10=10+4h | | 10-w=-10-3w | | 2p+10=24 | | 4+7g=6g | | 8x=-3y+-11 | | 5x-2-9x-8=6x-10x-13 | | 601=x-24 | | x+19x= | | 1+7k=10k+10 | | E-43=121 |